The Impact of Digital Marketing on Purchase Decision: A Field Study on Yemeni Food Manufacturing Companies from the Perspective of Customers in the Capital Municipality of Sana'a - Mohammed Ali Mohammed Al-Ansi; Mohammed Abdullah Al-Attas (University of Science and Technology, Sana’a, Yemen, 2025)
This study aims to determine the impact of digital marketing on purchasing decisions in Yemeni food manufacturing companies from the perspective of customers in the Capital Municipality of Sana’a. The study employed a descriptive-analytical approach to achieve its objectives and used a questionnaire as the primary tool for data collection. The study population consisted of customers of Yemeni food manufacturing companies, with a sample of 384 respondents from Sana’a. A convenience sampling method was used due to the absence of a defined sampling frame. Data were entered and coded using SPSS software. The results of the study revealed that, from the customers' perspective, Yemeni food manufacturing companies engage in digital marketing at a moderate level across all its dimensions. Furthermore, purchasing decisions were made at a high level across all dimensions. The study also found a statistically significant positive impact of digital marketing dimensions on customers' purchasing decisions for Yemeni food manufacturing companies. The study recommends that Yemeni food manufacturing companies place greater emphasis on digital marketing to influence consumer purchasing decisions. It also suggests strengthening this relationship by integrating the concepts of digital marketing and purchasing decisions into the company's business philosophy. Additionally, it highlights the importance of utilizing technology to predict and influence consumer behavior.